2022
DOI: 10.1039/d1nh00353d
|View full text |Cite
|
Sign up to set email alerts
|

A multiferroic vanadium phosphide monolayer with ferromagnetic half-metallicity and topological Dirac states

Abstract: Ferroelasticity, ferromagnetism, half-metallicity, and topological Dirac states are compelling properties highly sought in two-dimensional (2D) materials for advanced device applications. Here, we report first-principles prediction of a dynamically and thermally...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…Monolayer VP and VAs has an anisotropic rectangular lattice with an in-plane easy magnetization axis. 25,26 In this work, we proved that constructing Janus monolayer V 2 XN (X = P, As) can realize the easy-plane magnetism in a 2D square lattice. We first identified that FM state was the ground-state magnetic order for Janus monolayer V 2 XN.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…Monolayer VP and VAs has an anisotropic rectangular lattice with an in-plane easy magnetization axis. 25,26 In this work, we proved that constructing Janus monolayer V 2 XN (X = P, As) can realize the easy-plane magnetism in a 2D square lattice. We first identified that FM state was the ground-state magnetic order for Janus monolayer V 2 XN.…”
mentioning
confidence: 74%
“…Monolayer VP adopted a anisotropic rectangle lattice with lattice constant a = 4.219/4.453 Å and b = 3.420/4.443 Å by PBE/PBE+U calculations, which agrees well with previous works. 25,26 The large difference between the results in PBE and PBE+U calculations indicated the necessity to consider the electron correlation effect in structural relaxation of V-based 2D materials. The effective onsite repulsion U f of 2 ∼ 4 eV have been adopted for V-d orbitals in previous works.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A class of 2D materials that possess spontaneous ferroelasticity have been demonstrated to show multiple orientation variants after transition from the high-symmetry paraelastic (PE) phase into the lower-symmetry FE phase. , The nondiffusive switching between different FE variants can be triggered by the external mechanical stress, resulting in the nonzero FE strain (lattice deformation) as well as the strain-orientation dependent properties. , Especially, 2D FE materials with atomic thickness and high mechanical strength can sustain extraordinarily large FE strain, thereby having possibly tunable properties through FE strain engineering . For example, 2D FE transition metal dichalcogenide monolayers in the 1T′ phase can display a quantum spin Hall effect, , and rotational orientation dependent topological edge states appeared at the domain boundaries .…”
mentioning
confidence: 99%